Performance Evaluation of A Low Heat Rejection Diesel Engine for Different Insulation Levels - Can Haşimoğlu; Murat Ciniviz; M. Sahir Salman (Pamukkale University Journal of Engineering Sciences, 2010)
This experimental study focuses on investigating of effects of low heat rejection engine application to a diesel engine at different insulation levels. For this purpose cylinder head and valves of the test engine were thermally insulated with yttria-stabilized zirconia (Y2O3–ZrO2) layer at first stage. Then in addition to cylinder head and valves, pistons of the test engine were coated with the same material. Brake specific fuel consumption (BSFC), exhaust gas temperature (EGT), brake thermal efficiency and volumetric efficiency of the test engine were investigated for two different insulation levels. After the engine tests it was determined that BSFC was improved by 4 - 7.1 %, EGT was increased by 3.5 - 6.8 %, brake thermal efficiency was improved by 4.1-7.9 % and volumetric efficiency was increased by 0.9 - 2.6 % with LHR application. It was also determined that these improvements in engine performance are proportional with the insulation levels of the test engine.